Preparation and Evaluation of Nanoemulgels Containing a Combination of Grape Seed Oil and Anisotriazine as Sunscreen - Arianto, Anayanti; Lie, Desi Yet Lie; -, Sumaiyah; Bangun, Hakim Bangun (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Grape seed oil contains Vitamin E which acts as skin antioxidant and natural ultraviolet (UV) absorbent and anisotriazine is used as chemical absorbent. Sun protection factor (SPF) value of the sunscreen and physical stability can be increased using a combination of grape seed oil and anisotriazine as sunscreen material and preparation by nanotechnology. AIM: The objective of this study was to prepare and evaluate physical stability and in vitro SPF value of sunscreen nanoemulgel containing grape seed oil and anisotriazine. METHODS: Nanoemulgels containing 4% grape seed oil and anisotriazine (1.6% and 3.2%) were formulated by adding 2% of Carbopol 940 gel to the optimized nanoemulsions formulation with a ratio of nanoemulsion and gel 4:1. The nanoemulgels were evaluated physical stability during storage for 12 weeks at variations of temperature, centrifugation, and cycling test. SPF values of nanoemulgels were determined by UV–visible spectrophotometric method and compared to emulgel. Droplet morphology observation of nanoemulgel using transmission electron microscope. RESULTS: The results of this study showed that sunscreen nanoemulgel containing 4% grape seed oil and 3.2% anisotriazine had average droplet size of 187.5 nm, physically stable during experiment for 12 weeks at variation of temperature and after centrifugation and cycling test, but the sunscreen emulgel showed a phase separation. The SPF of nanoemulgel containing a combination of 4% grape seed oil and 3.2%, nanoemulgel without anisotriazine, and emulgel formulation was 19.325 ± 0.232, 11.169 ± 0.113, and 11.913 ± 0.161, respectively. Transmission electron microscopy analysis of droplet morphology showed that this nanoemulgel formulation formed a spherical globule. CONCLUSION: The sunscreen nanoemulgel formulation containing combination of 4% grape seed oil and 3.2% anisotriazine more stable than sunscreen emulgel during experiment for 12 weeks at room temperature and showed the SPF value higher compared to emulgel containing 4% grape seed oil and 3.2% anisotriazine and nanoemulgel without anisotriazine.